Peritoneal inclusion cyst resulting in intestinal obstruction:rare case report - M., Vijay Ganesh (International Surgery Journal, 2016)
Peritoneal inclusion cyst (PIC) is a rare cause of intestinal obstruction. This patient presented to us with all signs and symptoms of intestinal obstruction. On emergency laparotomy it appeared like a malignant lesion, which was resected and anastomosis done. HPE report proved it to be multi loculated peritoneal inclusion cyst. This case is presented for its rarity in itself, presenting as intestinal obstruction, in a male, that too without previous history of any surgery.